Prevalence and Multilocus Genotyping of Giardia lamblia in Cattle in Jiangxi Province, China: Novel Assemblage E Subtypes Identified - Li, Sen (Korean J Parasitol, 2020)
Giardia lamblia is a common enteric pathogen associated with diarrheal diseases. There are some reports of G. lamblia infection among different breeds of cattle in recent years worldwide. However, it is yet to know whether cattle in Jiangxi province, southeastern China is infected with G. lamblia. The objectives of the present study were to investigate the prevalence and examine the multilocus genotypes of G. lamblia in cattle in Jiangxi province. A total of 556 fecal samples were collected from 3 cattle breeds (dairy cattle, beef cattle, and buffalo) in Jiangxi province, and the prevalence and genotypes of G. lamblia were determined by the nested PCR amplification of the beta-giardin (bg) gene. A total of 52 samples (9.2%) were positive for G. lamblia. The highest prevalence of G. lamblia was detected in dairy cattle (20.0%), followed by that in beef cattle (6.4%), and meat buffalo (0.9%). Multilocus sequence typing of G. lamblia was performed based on sequences of the bg, triose phosphate isomerase and glutamate dehydrogenase loci, and 22, 42, and 52 samples were amplifiable, respectively, forming 15 MLGs. Moreover, one mixed G. lamblia infection (assemblages A and E) was found in the present study. Altogether, 6 novel assemblage E subtypes (E41*–E46*) were identified for the first time. These results not only provided baseline data for the control of G. lamblia infection in cattle in this southeastern province of China, but also enriched the molecular epidemiological data and genetic diversity of G. lamblia in cattle.